A DFT Study on Electronic and Structural Properties of Graphene Nanoribbons - I.K. Petrushenko (Журнал нано- та електронної фізики)
We carry out quantum chemistry calculations on armchair graphene nanoribbons (AGNRs) using density-functional theory. PVE/SVP results for the dependence of energies of the highest occupied (HOMO) and lowest unoccupied molecular orbitals (LUMO) as well as energy gaps on AGNR widths and lengths are presented. We compare the HOMO and LUMO energies of a series of AGNRs with those energies of fullerene C60 and its soluble derivative, PCBM, to ascertain whether it is possible to use such AGNRs as electron acceptors in organic solar cells. The influence of Stone-Wales defects embedded in the frameworks of AGNRs on their electronic properties is also studied.